2015
DOI: 10.1007/s00380-015-0644-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of preoperative regular physical activity on postoperative course after open abdominal aortic aneurysm surgery

Abstract: Early ambulation after open abdominal aortic aneurysm (AAA) surgery is assumed to play a key role in preventing postoperative complications and reducing hospital length of stay. However, the factors predicting early ambulation after open AAA surgery have not yet been sufficiently investigated. Here, we investigated which preoperative and intraoperative variables are associated with start time for ambulation in patients after open AAA surgery. A total of 67 consecutive patients undergoing open AAA surgery were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Good fitness levels are considered important to reduce hospital stay with no reduction in surgical mortality rates. 33 These facts still do not constitute evidence to support recommending exercise to patients with small aneurysms at surveillance, since few patients have been evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Good fitness levels are considered important to reduce hospital stay with no reduction in surgical mortality rates. 33 These facts still do not constitute evidence to support recommending exercise to patients with small aneurysms at surveillance, since few patients have been evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…(2016) 33 Case-control study. Patients were allocated to fit or unfit groups according to physical capacity.…”
Section: Risk Of Bias In Included Studiesmentioning
confidence: 99%
“…95 Another cohort study found AAA patients who exercised early in preparation for surgery compared to later in recovery from surgery had a significantly shorter LOS and time to attaining independence in sitting, standing, and walking. 96 While the studies had diversity of training programs and mixed results, they favor the use of the exercise component of prehabilitation and showed safety of exercise in AAA patients with no adverse events related to aneurysm.…”
Section: Preoperative Exercise Therapy/prehabilitationmentioning
confidence: 99%
“…This makes comparing results and data significantly difficult, with the added challenge of investigating different outcomes. Though there are papers that suggest patients who have increased physical activity levels pre-operatively, do better post-operatively than those who do not, this cannot be attributed to specific interventions and could be related to numerous other factors within their lifestyle, in addition to their activity levels [37][38][39][40] .…”
Section: Summary Of Current Evidence For Pre-operative Intervention For Aaasmentioning
confidence: 99%